Effects of kinesio taping applied over the biceps muscle on muscle activity and muscle fatigue - Bebek, G.; Ocak, Y.; Sözen, H. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Kinesio taping (KT) is commonly used to support muscle function, enhance performance, and reduce fatigue in both athletic and clinical settings. Understanding its effects on agonist and antagonist muscle groups during resistance exercises is essential for optimizing training and rehabilitation strategies. This study aimed to investigate the effects of kinesiotaping (KT) applied to the biceps brachii on the activation and fatigue of the biceps brachii (BB) and triceps brachii (TB) muscles during bicipital curl exercise.